2018
DOI: 10.18632/oncotarget.24556
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of macrophage polarization: implications for targeting tumor-associated macrophages

Abstract: The progression of cancer is a result of not only the growth of the malignant cells but also the behavior of other components of the tumor microenvironment (TME). Tumor-associated macrophages (TAMs) are key components of the TME that influence tumor growth and disease progression. TAMs can either inhibit or support tumor growth depending on their polarization to classically-activated macrophages (M1s) or alternatively-activated macrophages (M2s), respectively. Epigenetic regulation plays a significant role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 134 publications
(139 reference statements)
3
75
0
Order By: Relevance
“…3a-d), thus shifting the fraction of pro-inflammatory F4/80 + iNOS + downward and favoring an M2 phenotype. Our findings are in line with previous reports, whereby epigenetic regulation by HDIs could modulate numbers of mature MNC as well as their phenotype [27][28][29]. The novelty of this report is that MNC could be driven to transform to pro-or anti-inflammatory phenotypes, depending on the timing of HDI administration.…”
Section: Discussionsupporting
confidence: 92%
“…3a-d), thus shifting the fraction of pro-inflammatory F4/80 + iNOS + downward and favoring an M2 phenotype. Our findings are in line with previous reports, whereby epigenetic regulation by HDIs could modulate numbers of mature MNC as well as their phenotype [27][28][29]. The novelty of this report is that MNC could be driven to transform to pro-or anti-inflammatory phenotypes, depending on the timing of HDI administration.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have highlighted that macrophages are not exempt from these epigenetic modifications because they directly affect the polarization state of macrophages. (125)(126)(127)(128)(129) Aside from macrophagedepleting agents used in mice, such as clodronate-loaded liposomes or KC depletion by gadolinium chloride, several approaches have been proposed to influence the macrophage phenotype. Macrophage-targeting delivery methods for immunomodulatory drugs or silencing RNAs (siRNAs) include the use of nanoparticles, liposomes, glucan shell microparticles, and oligopeptide complexes.…”
Section: Spectra and Fluidity Of Macrophage Polarization Statesmentioning
confidence: 99%
“…It is also found that the normal cells show epigenetic changes once placed in the supernatant of tumour tissues, although it is not possible to determine who initiates this change. The interaction between the two is factual 21 . To illustrate this interaction, we used a simulated TME to verify the expression of ALKBH5 in ovarian cancer tissue and the related regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%